Perbandingan Pemikiran Demokrasi Pendidikan Paulo Freire dan Muhammad Athiyah Al-Abrasyi - Abdul Qiso, Ahmad; Nafisah, Ani (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2021)
In today's era, democratic education is a must for a nation, because democracy provides the best opportunities that can provide equal and fair opportunities, respect human dignity, and cooperation opportunities that can win all parties. The dream of quality education can only be realized in the realm of educational democracy. However, in reality democratic education in our educational practice has not been implemented seriously, students are still constrained by the current education system. This study will discuss the democratic thinking of education by Paulo Freire and Muhammad Athiyah Al-Abrasyi. The data was extracted by conducting a literature review, looking for literature either from books or journals that discussed the thoughts of the two great figures. The results of this research are according to Paulo Freire, democratic education or liberating education is education that will not be separated from the oppressed, will not treat them as 'unlucky people' and treat the oppressed as role models among the oppressors. The education of the oppressed is carried out by authentic generosity, humanist (not humanitarian) generosity, presenting itself as human education. Meanwhile, according to democracy, according to Muhammad Athiyah Al-Abrasyi, education is the idea of ​​a worldview that prioritizes rights and obligations as well as equal treatment for all citizens in the ongoing education process. Al-Abrasyi's thoughts on education democracy are in line with the concept of human freedom which leads to opportunity and equality in obtaining education.